2007
DOI: 10.1017/s1138741600006375
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Longevity of Volunteer Service: A Basic Alternative Proposal

Abstract: A problem for many organizations is the low continuity of volunteers. Diverse theoretical models have been developed to explain sustained volunteerism, but most of these models have focused on the study of welfare volunteerism and not have verified whether their results could be generalized to other types of volunteerism. In this study, we propose a basic model to explain sustained volunteerism in any type of volunteerism. The aim of this study is to examine this basic model empirically in a sample of socio-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 22 publications
3
5
0
2
Order By: Relevance
“…Overall, satisfaction with providing charitable care was the strongest predictor associated with providing charitable care in the office and the community. This is similar to studies in psychology that have found associations between participation in volunteer activities and satisfaction with the activity 26 , 29 . It has been suggested that because satisfaction with volunteering in an organization is associated with continued volunteer participation, organizations should provide incentives and positive environmental settings to increase volunteer satisfaction 29 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Overall, satisfaction with providing charitable care was the strongest predictor associated with providing charitable care in the office and the community. This is similar to studies in psychology that have found associations between participation in volunteer activities and satisfaction with the activity 26 , 29 . It has been suggested that because satisfaction with volunteering in an organization is associated with continued volunteer participation, organizations should provide incentives and positive environmental settings to increase volunteer satisfaction 29 .…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to studies in psychology that have found associations between participation in volunteer activities and satisfaction with the activity 26 , 29 . It has been suggested that because satisfaction with volunteering in an organization is associated with continued volunteer participation, organizations should provide incentives and positive environmental settings to increase volunteer satisfaction 29 . Organizations that rely on volunteer dentists should continually assess the satisfaction of their volunteers to help ensure the continuity of the relationships between the dentists and the organizations.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our success at establishing a mediational pathway which plausibly reflects real-world processes encouraged us to attempt a replication of these results in Study 2. Fuertes, 2007;Law & Shek, 2009;Okun & Sloane, 2002), echoing the widely reported intention-behavior gap in behavioral research (Sheeran, 2002;Sutton, 1998). Additionally, whether one volunteers is shaped by various practical barriers (e.g., time, distance, not being asked; Schuldt, Ferrara, & Wojcicki, 2001;Sundeen, Raskoff, & Garcia, 2007) which can prevent intentions from translating into behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A key difference between this and prior research is the reliance on volunteering intentions, rather than behavior, as an outcome variable. It should be noted that there is a well‐reported discrepancy between intentions to volunteer and volunteering behavior (de León & Fuertes, 2007; Law & Shek, 2009; Okun & Sloane, 2002), echoing the widely reported intention‐behavior gap in behavioral research (Sheeran, 2002; Sutton, 1998). Additionally, whether one volunteers is shaped by various practical barriers (e.g., time, distance, not being asked; Schuldt, Ferrara, & Wojcicki, 2001; Sundeen, Raskoff, & Garcia, 2007) which can prevent intentions from translating into behavior.…”
Section: Discussionmentioning
confidence: 99%